Knowledge, attitude, and practices regarding child abuse and neglect among members of different occupations in belagavi: A questionnaire study - Chandrashekhar Badakar (International Journal of Pedodontic Rehabilitation, 2020)
Introduction: Child abuse and neglect is a global phenomenon and it can occur in a child's home or in organizations, schools, or communities. Child abuse and neglect has an impact on individuals, families, and communities, particularly all domains of children's development-physical, psychological, cognitive, behavioral, and social. The aim of the survey was to assess and compare the knowledge, attitude, and practices of child abuse and neglect amid the members of the occupations doctors, police, advocates, and teachers residing in Belagavi city. Materials and Methods: A questionnaire with 16 questions regarding the knowledge, attitude, and practice about child abuse and neglect was distributed to 200 members of various professions doctors, police, advocates, and teachers. Results: The response showed that teachers (98%) had better knowledge than the other group and all the members had a positive attitude. Lawyers (63%) had the most minimum practice toward child abuse and neglect. Conclusion: The results of this study showed that all the members involved in the study has a positive attitude toward tackling child abuse and neglect with teachers having the most knowledge and lawyers with minimum practice.